Pengembangan Podcast sebagai Media Pembelajaran pada Mata Pelajaran Bahasa Indonesia untuk Siswa SD Kelas IV - Amirul Fikri; Abna Hidayati; Ulfia Rahmi; Septriyan Anugrah (Dinasti Research, 2023)
The development of podcasts as learning media is carried out as a form of effort in overcoming problems in learning activities, where the lack of learning media used by teachers has an impact on students' lack of motivation in learning. This study aims to develop podcasts as learning media for grade IV Indonesian Language Subjects in order to produce media that is appropriate, practical and effective for use by teachers and students. This type of research uses Research and Development (R&D) research with the Hannadfin & Peck research model. This development model consists of 3 stages in each stage there is an evaluation, namely needs analysis, design, development, and implementation. Based on the assessment results from the media validator and material validator, an average material validation result of 4.9 was categorized as